Genes Activated by Vibrio cholerae upon Exposure to Caenorhabditis elegans Reveal the Mannose-Sensitive Hemagglutinin To Be Essential for Colonization - Cornelia List (American Society for Microbiology, 2018)
ABSTRACT During its life cycle, the facultative human pathogen Vibrio cholerae, which is the causative agent of the diarrheal disease cholera, needs to adapt to a variety of different conditions, such as the human host or the aquatic environment. Importantly, cholera infections originate from the aquatic reservoir where V. cholerae persists between the outbreaks. In the aquatic environment, bacteria are constantly threatened by predatory protozoa and nematodes, but our knowledge of the response pathways and adaptation strategies of V. cholerae to such stressors is limited. Using a temporally controlled reporter system of transcription, we identified more than 100 genes of V. cholerae induced upon exposure to the nematode Caenorhabditis elegans, which emerged recently as a valuable model for environmental predation during the aquatic lifestyle of V. cholerae. Besides others, we identified and validated the genes encoding the mannose-sensitive hemagglutinin (MSHA) type IV pilus to be significantly induced upon exposure to the nematode. Subsequent analyses demonstrated that the mannose-sensitive hemagglutinin is crucial for attachment of V. cholerae in the pharynx of the worm and initiation of colonization, which results in growth retardation and developmental delay of C. elegans. Thus, the surface adhesion factor MSHA could be linked to a fitness advantage of V. cholerae upon contact with bacterium-grazing nematodes. IMPORTANCE The waterborne diarrheal disease cholera is caused by the bacterium Vibrio cholerae. The facultative human pathogen persists as a natural inhabitant in the aquatic ecosystem between outbreaks. In contrast to the human host, V. cholerae requires a different set of genes to survive in this hostile environment. For example, predatory micrograzers are commonly found in the aquatic environment and use bacteria as a nutrient source, but knowledge of the interaction between bacterivorous grazers and V. cholerae is limited. In this study, we successfully adapted a genetic reporter technology and identified more than 100 genes activated by V. cholerae upon exposure to the bacterium-grazing nematode Caenorhabditis elegans. This screen provides a first glimpse into responses and adaptational strategies of the bacterial pathogen against such natural predators. Subsequent phenotypic characterization revealed the mannose-sensitive hemagglutinin to be crucial for colonization of the worm, which causes developmental delay and growth retardation.